(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper narrates the study of use of Google Groups for creating learning environment. Google Gatherings is assistance from Google that gives talk gatherings to individuals sharing regular interests. It is easy to share latest news, announcements, assignments, web links, class nots, reading materials etc. vie Google group. It is easy to create and manage the google groups through the option Group Settings. Google Groups are very user friendly. Google groups are very useful in collaborative teamwork, e learning, projects making etc.